Comparison of graph and animation: An unbalanced battle over two decades - Zhuang, Qianhong; Liu, Xiaobin (Frontiers in Psychology, 2022)
Numerous studies have produced contradictory findings about whether static or animated format is the better instructional tool. With a comparison between graphs and animations that has a genuine impact on learning and teaching, this review provides a comprehensive examination of (a) the theoretical foundations of visualised learning, (b) influencing factors, and (c) prospective future studies.